Numerical Analysis of Flow Velocity and Performance Test of Cross-Flow Turbine (500 W) - Kyaw, Sandar; Swe, War War Min; Soe, Aung Kyaw; Latt, Aung Ko (AI Society & STMIK Indonesia, 2024)
The purpose of this study is to analyze the flow velocity and assess the performance of a cross-flow turbine through numerical simulations and performance tests. Using computational fluid dynamics (CFD), the flow patterns and velocity distributions around the turbine blades to gain insights into the turbine's hydrodynamic behavior. In the experimental phase, constructed a prototype of the cross-flow turbine and tested it in a water flume, measuring key performance metrics such as power output and efficiency.The test were performed under design flow condition. The numerical results were validated with performance tests. The numerical analysis revealed critical areas of flow separation and turbulence, which were consistent with the observed experimental data.